Transformative Communication Technologies The Accountability Challenge (36th Böhm-Bawerk-Lectures) - Mansell, Robin (Kleine Medienreihe, 2018)
"This booklet documents the 36th Boehm-Bawerk Lecture, presented by Prof. Robin Mansell on October 31, 2017 as a ceremonial opening ceremony for the Institute of Media, Society and Communication at the Faculty of Social and Political Sciences. "